Role of the Third Place in Building Communities and Social Capital :Contributions of Coffee Shops as Third Places in Kuwait - kandari, Hissah Abdullah; Chaudry, Abdus Sattar (International Journal of Knowledge Content Development & Technology, 2023)
Third places are those that offer a space outside of work and home for people to escape the stress associated with the primary spaces of their lives. Through social interactivity these help in acquiring some emotional support provided by a close and intimate attachment. Such social support can turn into social resources for individuals and can lead to forming communities that may become incubators for social capital through regular visits to shared socializing places. This paper focuses on social interaction that takes place through the third place and the communities that are being created as a contributing factor to knowledge management. The study being reported in this paper investigated the role of coffee shops as third places in building communities and social capital in Kuwait. A mixed-method approach was used to conduct the study. These methods included qualitative methods such as extended conversations in the form of semi-structured interviews and quantitative methods of using questionnaires distributed to coffee shop staff and visitors. Results indicated that importance attached to providing facilities by coffee shops reflected that the owners perceived these as third places. The facilities attracted customers to coffee houses where interactions took place that helped to build communities. The pattern of visits by customers showed that mostly they come in groups and have meetings and gatherings that facilitated and encouraged interactions. The communities that are being built in the coffee shops are indicative of these being perceived as third places by owners, customers, and staff. This study shows the potential of coffee shops as a major sector of the food industry promising a valuable contribution in transformation and transition to a knowledge-based economy in Kuwait.